The development of a Modular Accessible Musical Instrument Technology Toolkit using action research - Ward, Asha (Frontiers in Computer Science, 2023)
Within the field of digital musical instruments there have been a growing number of technological developments aimed at addressing the issue of accessibility to music making for disabled people. This paper summarizes the development of one such technological system -The Modular Accessible Musical Instrument Technology Toolkit (MAMI Tech Toolkit). The four tools in the toolkit and accompanying software were developed over five years using an action research methodology. A range of stakeholders across four research sites were involved in the development. This paper outlines the methodological process, the stakeholder involvement, and how the data was used to inform the design of the toolkit. The accessibility of the toolkit is also discussed alongside findings that have emerged from the process. This paper adds to the established canon of research around accessible digital musical instruments by documenting the creation of an accessible toolkit grounded in both theory and practical application of third-wave human computer interaction methods. This paper contributes to the discourse around the use of participatory and iterative methods to explore issues with, and barriers to, active music making with music technology. Outlined is the development of each of the novel tools in the toolkit, the functionality they offer, as well as the accessibility issues they address. The paper advances knowledge around active music making using music technology, as well as in working with diverse users to create these new types of systems.